Serotonin-dependent kinetics of feeding bursts underlie a graded response to food availability in C. elegans - Kyung Suk Lee (Nature Portfolio, 2017)
Regulating food intake is an important physiological mechanism. Here, the authors use a custom microfluidic device to investigate feeding dynamics inC. elegans, and identify roles of serotonergic neurons in regulating bursts of feeding in response to food availability.